Covid-19 and ecotourism prospect: Malaysia and Indonesia perspectives - Yuary Farradia, Yuary Farradia; Harun, Amran (Penerbit UTHM, 2022)
The coronavirus (Covid 19) has a significant impact on all businesses in Asia, the Pacific region, and the rest of the world. Indeed, apart from health effects, the Covid 19 pandemic has significant economic effects worldwide. Tourism is the most significantly affected business by COVID-19. As a major economic sector and source of foreign exchange earnings in many countries in Asia, the sudden fall in tourist arrivals has severe economic and social consequences within and beyond tourism. Helble and Fink (2020) stated that one strategy for countries' tourism recovery could be implemented through travel bubbles or the concept of a green corridor. Travel bubbles with the green concept become one of the strategies from countries such as Indonesia and Malaysia.